Barriers and facilitators to implementing simulation into pharmacy programs globally - Harjit K. Singh; Vivienne Mak; Keith Sewell; Daniel T. Malone (Taylor & Francis Group, 2023)
Abstract Background MyDispense is a simulation software developed by Monash University that has been utilized by over 200 institutions worldwide to educate pharmacy students. However, little is known about the processes by which it is used to teach dispensing skills to students and how they use it to facilitate critical thinking in an authentic environment. This study aimed to understand and investigate how simulations are used to teach dispensing skills in pharmacy programs globally, and to determine the opinions, attitudes and experiences of pharmacy educators towards MyDispense and other simulation software within their pharmacy program. Methods Purposive sampling was used to identify pharmacy institutions for the study. A total of 57 educators were contacted, 18 responded to the study invitation, 12 were MyDispense users and 6 were non-users. Two investigators conducted an inductive thematic analysis to generate key themes and subthemes to provide insight into the opinions, attitudes and experiences towards MyDispense and other simulation software used specifically for dispensing within pharmacy programs. Results 26 pharmacy educators were interviewed, of which 14 were individual interviews and four were group interviews. Intercoder reliability was investigated and a Kappa coefficient of 0.72 indicated substantial agreement between both coders. Five main themes were identified: "dispensing and counseling", which encompassed discussions about how dispensing techniques were taught, the time allocated for students to practice their skills and the use of software other than MyDispense; "description of MyDispense use" includes discussions about the setup of the software, how dispensing skills were taught prior to using MyDispense as well as its use in student assessments; "barriers to MyDispense use", covers discussions about the obstacles users have faced; "facilitators to use MyDispense", includes discussion about the various motivators to using MyDispense and lastly "future use and suggested improvements" of MyDispense are covered by the interviewees. Conclusion The initial outcomes of this project evaluated the awareness and utilization of MyDispense and other dispensing simulations by pharmacy programs globally. By addressing the barriers of use, promotion of the sharing of MyDispense cases can assist in creating more authentic assessments, as well as improving staff workload management. The outcomes of this research will also facilitate the development of a framework for MyDispense implementation, thus streamlining and improving the uptake of MyDispense by pharmacy institutions globally.